Cold Acclimation of Hedera helix: Evidence for a Two Phase Process - Steponkus, Peter L. (1971)
The light-enhanced production and accumulation of sugars is only one step in the process of cold acclimation in Hedera helix L. var. Thorndale (English ivy). Applications of 2,4-dinitrophenol to plants with different portions exposed to light and dark indicated that the mere presence or accumulation of the light-generated promoters did not invoke an increase in hardiness. Kinetics of cold acclimation during alternating periods of light and dark also indicate that the light stimulation of cold acclimation is only a partial component of the total process. Incubation on 50 mm solutions of sucrose can replace the light requirement. A second phase which can proceed in the dark is thought to result in the production of proteins which, due to an altered composition or configuration, have a greater capacity to bind sugars. This is evidenced by the fact that protein from cold acclimated tissue exhibited a higher sugar-binding capacity than protein from nonacclimated tissue. Furthermore, the two phases can proceed independently of each other, but only upon complementation of the products of the two phases is an increase in cold hardiness manifested.